'Draw your pelvis' test for assessing pelvic schema in people with Parkinsonʼs disease: a validity and reliability study. (3rd April 2019) - Abraham, Amit; Wright, Gene N.; Morrison, Margaret W.; Hart, Ariel; Dickstein, Ruth; Hackney, Madeleine E.
Abstract: Aim: Body schema (i.e., the mental representation of the body and its parts) is important for cognitive and motor functions, with the pelvis constituting a core element in such schema. Although people with Parkinsonʼs disease exhibit misperceptions and deficits in body schema, there are currently no published tools available for assessing pelvic schema in this population. This study aimed to develop and establish feasibility, reliability, and validity of a novel drawing test − 'Draw Your Pelvis' − for assessing pelvic schema in people with Parkinsonʼs disease. Materials and methods: Twenty people with idiopathic Parkinsonʼs disease (Hoehn &Yahr stages I–III; M age: 65.75 ± 10.13) volunteered and were asked to manually draw a picture of their pelvis. Drawings were assessed and scored by 13 blinded raters over two sessions. Intra- and inter-rater reliability and content and criterion validity were investigated. Results: The 'Draw Your Pelvis' test is shown to be feasible and quick to administer, with excellent inter-rater reliability for consistency (0.954–0.968) and absolute agreement (0.946–0.961). It also demonstrates good-excellent (0.614–0.950) intra-rater reliability, and is content valid. Conclusions: The 'Draw Your Pelvis' test holds potential for clinicians and researchers in assessing pelvic schema and its deficits in people with Parkinsonʼs disease. In addition, this test could be used for investigating the effect of therapeutic interventions on body schema in this population. Future studies should explore this test in additional populations.